LEKSIKON TATA BOGA DALAM MASYARAKAT MELAYU PADANG TIKAR - Neneng Neneng; Deden Ramdani; Agus Syahrani (Universitas Tanjungpura, 2021)
AbstractLanguage has an important role in both spoken and written. every language has meaning. The unit of meaningful language form is a lexeme. The purpose of this study is to describe the culinary lexicon in the Padang Tikar Malay community including the form of the lexicon, lexical meaning, cultural meaning, and implementation in Indonesian language learning in accordance with the 2013 curriculum. The research form used was qualitative with descriptive method. The source of data in this study is the speech of the native Malay community of Padang Tikar. Data collection techniques used are face-to-face, note-taking, and recording techniques. Techniques to test the validity of the data are referential adequacy and triangulation. Based on the analysis of the results of the data found as many as 60 data on the culinary lexicon which is divided from 27 forms of lingual units in the form of phrases 32 monomorphemic data 17 lexical meaning data 7 cultural meaning data . This study describes a lesson plan that will be carried out in schools using the Indonesian language lesson plan 2013 curriculum class VII odd semester regarding procedural text.Keywords: lexicon, cullinary art, Malay Society Padang Tikar